Currarino’s syndrome. A case report (Colombia Medica, 2009)
The Currarino’s syndrome is a rare inherited disorder. The complete form is characterized by the presence of ano-rectal malformation (usually stenosis), presacral mass and bone defects of the sacrum. The most important symptom is the presence of constipation since birth. A 13 month old patient with chronic and severe constipation is presented. Among the studies the presence of hemisacrum and anterior meningocele were found, both findings consistent with a mild form of Currarino’s syndrome. A conservative management with polietilenglycol oral (PEG®), was initiated with an excellent response to treatment. The presentation of the case with a review of current literature is given to the medical staff in order to publicize the syndrome, as well as to emphasize key points that create suspicion of their presence and the different therapeutic options for its approach.